Lamiaceae Family Plants as Natural Solutions for Inflammation and Blood Sugar Management - Lagouri, Vasiliki; Tebbi, Sara Oumenoune; Caseiro, Armando; Trapali, Maria (European Scientific Journal, ESJ, 2024)
The Lamiaceae family, including common herbs like rosemary and mint, is being investigated for its potential health benefits. In addition to numerous health benefits, research is looking into these plants' anti-inflammatory qualities and potential impacts on blood sugar regulation. More specifically, the Greek endemic Lamiaceae plants are proven to be of great importance, regarding their bioactive compounds and the antioxidant, antidiabetic and anti-inflammatory properties they have. The study's objective was to compile information from the literature regarding the anti-inflammatory, antidiabetic, and antioxidant properties of Origanum rotundifolium, Rosmarinus officinalis, Lavendula angustifolia, and Thymus serpyllum. Lavender angustifolia is used for many traditional medical and cosmetic products. Several studies demonstrated strong anti-inflammatory mechanisms exhibited by Rosmarinus officinalis. Leukocyte migration was found to be significantly inhibited in vivo by rosemary essential oil and extract. Changes in the gut microbiota induced by essential oils rosemary as prebiotics in mice regulated cardiovascular and metabolic factors, which focus on the potential of these nutraceuticals for reducing Ischemic heart disease risk in patients affected by type-2 diabetes mellitus. A mixture of Origanum majorana and Origanum vulgare plants investigated antidiabetic activities in zebrafish. The Lamiaceae family provides a natural source of substances that may be used in functional foods. These functional meals have the potential to improve general health and help manage chronic illnesses. The precise mechanisms of action of these plants and the best doses for use in functional food applications require more investigation.